Hepatoprotective effect of licorice, the root of Glycyrrhiza uralensis Fischer, in alcohol-induced fatty liver disease. Issue 1 (December 2015) - Jung, Jae-Chul; Lee, Yun-Hee; Kim, Sou; Kim, Keuk-Jun; Kim, Kyung-Mi; Oh, Seikwan; Jung, Young-Suk
Abstract Background Our previous study suggested that licorice has anti-inflammatory activity in lipopolysaccharide-stimulated microglial cells and anti-oxidative activity intert -butyl hydroperoxide–induced oxidative liver damage. In this study, we evaluated the effect of licorice on chronic alcohol-induced fatty liver injury mediated by inflammation and oxidative stress. Methods Raw licorice was extracted, and quantitative and qualitative analysis of its components was performed by using LC–MS/MS. Mice were fed a liquid alcohol diet with or without licorice for 4 weeks. Results We have standardized 70 % fermented ethanol extracted licorice and confirmed by LC-MS/MS as glycyrrhizic acid (GA), 15.77 ± 0.34 μg/mg; liquiritin (LQ), 14.55 ± 0.42 μg/mg; and liquiritigenin (LG), 1.34 ± 0.02 μg/mg, respectively. Alcohol consumption increased serum alanine aminotransferase and aspartate aminotransferase activities and the levels of triglycerides and tumor necrosis factor (TNF)-α. Lipid accumulation in the liver was also markedly induced, whereas the glutathione level was reduced. All these alcohol-induced changes were effectively inhibited by licorice treatment. In particular, the hepatic glutathione level was restored and alcohol-induced TNF-α production was significantly inhibited by licorice. Conclusion Taken together, our data suggests that protective effect of licorice against alcohol-induced liver injury may be attributed to its anti-inflammatory activity and enhancement of antioxidant defense.